Joint and elastic wave element
By forming a high oxygen ratio amorphous layer between the piezoelectric material substrate and the support substrate, and directly bonding with neutral beam activation, the problem of peeling caused by low oxygen ratio in the bonding layer in the prior art is solved, and the problem of peeling is achieved Higher bonding strength and insulation.
Patent Information
- Application Number
- CN201980067483.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-10-17
- Filing Date
- 2019-08-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2039-08-23
AI Technical Summary
In the prior art, it is difficult to firmly and stably bond the piezoelectric material substrate to the support substrate through a silicon oxide bonding layer containing a low oxygen ratio, and peeling is prone to occur.
The composition of the first bonding layer and the second bonding layer is Si(1-x)Ox and Si(1-y)Oy, wherein 0.008≤x≤0.408 and 0.008≤y≤0.408 are formed between them, and an amorphous layer is formed. The oxygen ratio of the amorphous layer is higher than both, activated by neutral beams and bonded directly.
The insulating property and bonding strength of the bonding layer are improved, and the peeling of the piezoelectric material substrate during grinding and processing is prevented.
Smart Images

Figure CN112840563B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a bonded body of a piezoelectric material substrate and a supporting substrate, and an elastic wave element. Background Art
[0002] There are known elastic wave devices such as surface acoustic wave devices that can function as filter elements and oscillators used in mobile phones, Lamb wave devices using piezoelectric thin films, and thin film resonators (FBAR: Film Bulk Acoustic Resonator). As such elastic wave devices, there are known elastic wave devices in which a support substrate and a piezoelectric substrate that propagates surface acoustic waves are bonded together, and comb-shaped electrodes that can excite surface acoustic waves are provided on the surface of the piezoelectric substrate. By bonding a support substrate having a smaller thermal expansion coefficient than the piezoelectric substrate to the piezoelectric substrate in this way, changes in the size of the piezoelectric substrate when the temperature changes are suppressed, and changes in the frequency characteristics of the surface acoustic wave device are suppressed.
[0003] It is known that when a piezoelectric substrate is bonded to a silicon substrate, a silicon oxide film is formed on the surface of the piezoelectric substrate, and the piezoelectric substrate and the silicon substrate are directly bonded via the silicon oxide film (Patent Document 1). During this bonding, a plasma beam is irradiated on the surface of the silicon oxide film and the surface of the silicon substrate to activate the surface and perform direct bonding (plasma activation method).
[0004] In addition, it is known that the surface of the piezoelectric substrate is made rough, a filling layer is provided on the rough surface to flatten it, and the filling layer is bonded to the silicon substrate via an adhesive layer (Patent Document 2). In this method, epoxy or acrylic resin is used in the filling layer and the adhesive layer, and by making the bonding surface of the piezoelectric substrate rough, the reflection of the bulk wave is suppressed and the parasitic signal is reduced.
[0005] Also known is a direct bonding method of the so-called FAB (Fast Atom Beam) system (Patent Document 3). In this method, each bonding surface is irradiated with a neutralized atomic beam at room temperature for activation, thereby performing direct bonding.
[0006] On the other hand, Patent Document 4 describes that a piezoelectric material substrate is directly bonded to a support substrate made of ceramic (aluminum oxide, aluminum nitride, silicon nitride) via an intermediate layer instead of directly bonding to a silicon substrate. The intermediate layer is made of silicon, silicon oxide, silicon nitride, or aluminum nitride.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: U.S. Patent No. 7213314B2
[0010] Patent Document 2: Japanese Patent No. 5814727
[0011] Patent Document 3: Japanese Patent Application Laid-Open No. 2014-086400
[0012] Patent Document 4: Japanese Patent No. 3774782
[0013] Patent Document 5: PCT / JP2018 / 011256 Summary of the invention
[0014] Depending on the purpose of the bonded body, it is desirable to improve the insulation by increasing the resistance in the bonding layer. For example, in the case of an elastic wave element, noise and loss can be reduced by improving the insulation of the bonding layer. Therefore, the applicant of the present application disclosed that a bonding layer with high insulation is formed by making the bonding layer composed of silicon oxide with a low oxygen ratio (Patent Document 5).
[0015] However, it is sometimes difficult to firmly and stably bond a piezoelectric material substrate to a support substrate via a bonding layer containing silicon oxide having a low oxygen ratio, and peeling may occur when the piezoelectric material substrate is processed by polishing or the like.
[0016] An object of the present invention is to firmly and stably bond a piezoelectric material substrate to a supporting substrate via a bonding layer containing silicon oxide having a low oxygen ratio.
[0017] The present invention is characterized in that it has:
[0018] A supporting substrate;
[0019] Piezoelectric material substrate;
[0020] The first bonding layer is disposed on the support substrate and is composed of Si (1-x) O x (0.008≤x≤0.408);
[0021] The second bonding layer is disposed on the piezoelectric material substrate and is composed of Si (1-y) O y (0.008≤y≤0.408); and
[0022] an amorphous layer, the amorphous layer being disposed between the first bonding layer and the second bonding layer,
[0023] The oxygen ratio in the amorphous layer is higher than the oxygen ratio in the first bonding layer and the oxygen ratio in the second bonding layer.
[0024] Furthermore, the present invention relates to an elastic wave element, characterized in that:
[0025] The invention comprises: the bonded body and electrodes provided on the piezoelectric material substrate.
[0026] Effects of the Invention
[0027] According to the present invention, a piezoelectric material substrate can be firmly and stably bonded to a supporting substrate via a bonding layer containing silicon oxide having a low oxygen ratio. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 In the figure, (a) represents a piezoelectric material substrate 1, (b) represents a state where a second bonding layer 2 is provided on the piezoelectric material substrate 1, and (c) represents a state where a surface 2a of the second bonding layer 2 is activated by a neutral beam A to form an activated surface 5.
[0029] Figure 2 In the drawings, (a) shows a state where the first bonding layer 4 is provided on the supporting substrate 3 , and (b) shows a state where the surface 4 a of the first bonding layer 4 is activated by the neutral beam B to form an activated surface 6 .
[0030] Figure 3 In the figure, (a) shows a state where the first bonding layer 4 and the second bonding layer 2 are in contact with each other, and (b) shows a state where the first bonding layer 4A and the second bonding layer 2A are bonded to produce a bonded body 8 .
[0031] Figure 4 In the drawings, (a) shows a state where the piezoelectric material substrate 1A is thinned by processing, and (b) shows a state where the electrode 9 is provided on the piezoelectric material substrate 1A.
[0032] Figure 5 In the drawings, (a) shows a state where the first bonding layer 4 and the second bonding layer 2 are in contact with each other, and (b) shows a state where the first bonding layer 4A and the second bonding layer 2A are bonded to produce a bonded body 18 .
[0033] Figure 6 In the drawings, (a) shows a state where the piezoelectric material substrate 1A is thinned by processing, and (b) shows a state where the electrode 9 is provided on the piezoelectric material substrate 1A. DETAILED DESCRIPTION
[0034] Hereinafter, the present invention will be described in detail with reference to the drawings as appropriate.
[0035] like Figure 1 As shown in (a), the piezoelectric material substrate 1 has a pair of main surfaces 1a and 1b. Figure 1 As shown in (b), the second bonding layer 2 is formed on the main surface 1a of the piezoelectric material substrate 1. Figure 1 As shown in (c), the surface 2a of the second bonding layer 2 is irradiated with a neutral beam as indicated by arrow A, so that the surface 2a of the bonding layer 2 is activated to form an activated surface 5.
[0036] On the other hand, Figure 2 As shown in (a), a first bonding layer 4 is formed on the main surface 3a of the support substrate 3. Figure 2 As shown in (b), the surface 4a of the bonding layer 4 is irradiated with a neutral beam as indicated by arrow B, so that the surface 4a of the bonding layer 4 is activated to form an activated surface 6.
[0037] Next, if Figure 3 As shown in (a), the active surface 6 of the first bonding layer 4 and the active surface 5 of the second bonding layer 2 are directly contacted and pressure is applied, thereby Figure 3 As shown in (b), a bonded body 8 is obtained. Here, by controlling the output or irradiation time of the neutral beams A and B, an amorphous layer 7 can be generated along the bonding interface between the active surface 6 of the first bonding layer 4 and the active surface 5 of the second bonding layer 2. Figure 3 As shown in (b), an amorphous layer 7 is generated along the interface between the first bonding layer 4A and the second bonding layer 2A.
[0038] In a preferred embodiment, the surface 1b of the piezoelectric material substrate 1 of the bonded body 8 is further ground. Figure 4 As shown in (a), the thickness of the piezoelectric material substrate 1A is reduced to obtain a bonded body 8A. 1c is a polished surface.
[0039] Figure 4 In (b), predetermined electrodes 9 are formed on polished surface 1 c of piezoelectric material substrate 1A, thereby manufacturing elastic wave device 10 .
[0040] Figure 5 , Figure 6 In the embodiment, an intermediate layer 12A is provided between the piezoelectric material substrate 1 and the second bonding layer 2 , and an intermediate layer 12B is provided between the support substrate 3 and the first bonding layer 4 .
[0041] That is, Figure 5 As shown in (a), an intermediate layer 12A and a second bonding layer 2 are sequentially formed on the main surface 1a of the piezoelectric material substrate 1. Next, a neutral beam is irradiated on the surface of the bonding layer 2 to activate the surface of the bonding layer 2A to form an activated surface 5. An intermediate layer 12B and a first bonding layer 4 are sequentially formed on the main surface 3a of the support substrate 3. Next, a neutral beam is irradiated on each surface of the bonding layers 2 and 4 to activate each surface of each bonding layer to form activated surfaces 5 and 6.
[0042] Next, if Figure 5 As shown in (a), the active surface 6 of the first bonding layer 4 and the active surface 5 of the second bonding layer 2 are directly contacted and pressure is applied, thereby Figure 5As shown in (b), a bonded body 18 is obtained. Here, by controlling the output and irradiation time of the neutral beams A and B, an amorphous layer 7 can be generated along the bonding interface between the active surface 6 of the first bonding layer 4 and the active surface 5 of the second bonding layer 2 .
[0043] In a preferred embodiment, the surface 1b of the piezoelectric material substrate 1 of the bonded body 18 is further ground. Figure 6 As shown in (b), the thickness of the piezoelectric material substrate 1A is reduced to obtain a bonded body 18A. 1c is a polished surface.
[0044] Figure 6 In (b), predetermined electrodes 9 are formed on polished surface 1 c of piezoelectric material substrate 1A, thereby manufacturing elastic wave device 20 .
[0045] In the present invention, the support substrate may be formed of a single crystal or a polycrystal. The material of the support substrate is preferably selected from the group consisting of silicon, silicon aluminum oxynitride ceramics, sapphire, cordierite, polyaluminum sapphire and alumina. Alumina is preferably translucent alumina.
[0046] From the viewpoint of bonding strength, the relative density of the support substrate is preferably 99.5% or more, and may be 100%. The relative density is measured by the Archimedean method. The method for preparing the support substrate is not particularly limited, but a sintered body is preferred.
[0047] The silicon may be single crystal silicon or polycrystalline silicon, or may be high resistance silicon.
[0048] Silical nitride ceramics are ceramics obtained by sintering a mixture of silicon nitride and aluminum oxide, and have the following composition.
[0049] Si 6-z Al z O z N 8-z
[0050] That is, the sialon ceramic has a composition in which aluminum oxide is mixed in silicon nitride, and z represents the mixing ratio of aluminum oxide. z is more preferably not less than 0.5. In addition, z is more preferably not more than 4.0.
[0051] Sapphire is a single crystal having a composition of Al2O3, and alumina is a polycrystal having a composition of Al2O3. Cordierite is a ceramic having a composition of 2MgO·2Al2O3·5SiO2. Mullite is a ceramic having a composition ranging from 3Al2O3·2SiO2 to 2Al2O3·SiO2.
[0052] The material of the piezoelectric material substrate is not limited as long as it has the required piezoelectricity, and is preferably a single crystal having a composition of LiAO3. Here, A is one or more elements selected from the group consisting of niobium and tantalum. Therefore, LiAO3 can be lithium niobate, lithium tantalate, or a lithium niobate-lithium tantalate solid solution.
[0053] In the present invention, a first bonding layer is provided on the support substrate, and a second bonding layer is provided on the piezoelectric material substrate. The composition of the first bonding layer is Si (1-x) O x (0.008≤x≤0.408). The composition of the second bonding layer is Si (1-y) O y (0.008≤y≤0.408).
[0054] This composition is a composition in which the oxygen ratio is significantly lower than that of SiO2 (corresponding to x=0.667). (1-x) O x The first bonding layer and the Si (1-y) O y By bonding the piezoelectric material substrate to the support substrate through a second bonding layer having a thickness of (0.008≤y≤0.408), the insulation properties in these bonding layers can be improved.
[0055] In the Si forming each bonding layer (1-x) O x 、Si (1-y) O y In the composition, if x and y are less than 0.008, the resistance in the bonding layer is reduced and the desired insulation cannot be obtained. Therefore, x and y are set to be above 0.008, preferably above 0.010, more preferably above 0.020, and particularly preferably above 0.024. In addition, if x and y are greater than 0.408, the bonding strength decreases and the peeling of the piezoelectric material substrate is likely to occur. Therefore, x and y are set to be below 0.408, more preferably below 0.225.
[0056] The resistivity of each bonding layer is preferably 4.8×10 3 Ω·cm or more, more preferably 5.8×10 3 Ω·cm or more, particularly preferably 6.2×10 3 On the other hand, the resistivity of the bonding layer is usually 1.0×10 8 Ω·cm or less.
[0057] The thickness of each bonding layer is not particularly limited, but is preferably 0.01 to 10 μm, more preferably 0.01 to 0.5 μm, from the viewpoint of production cost.
[0058] The film forming method of each bonding layer is not limited, and examples thereof include sputtering, chemical vapor deposition (CVD), and evaporation. Here, it is particularly preferred that when the sputtering target is Si reactive sputtering, the oxygen ratio (x, y) of each bonding layer can be controlled by adjusting the amount of oxygen flowing into the chamber.
[0059] The specific manufacturing conditions of each bonding layer depend on the chamber specifications and are therefore appropriately selected. In a preferred example, the total pressure is 0.28 to 0.34 Pa and the oxygen partial pressure is 1.2×10 ―3 ~5.7×10 -2 Pa, and the film forming temperature is set to room temperature. In addition, as the Si target, Si doped with B can be exemplified. As described later, the amount of B (boron) as an impurity in the interface with the first bonding layer and the interface with the second bonding layer is controlled to be 5×10 18 atoms / cm 3 ~5×10 19 atoms / cm 3 Thereby, the insulation in the bonding layer can be ensured more reliably.
[0060] In the present invention, the active surface of the first bonding layer and the active surface of the second bonding layer are directly bonded. In other words, a bonding interface is provided along the interface between the first bonding layer and the second bonding layer. Therefore, the arithmetic mean roughness Ra of each active surface of each bonding layer is preferably less than 1 nm, more preferably less than 0.3 nm. Thus, the bonding strength is further improved.
[0061] The bonded body of the present invention comprises: an amorphous layer generated between the first bonding layer and the second bonding layer, and the oxygen ratio in the amorphous layer is higher than the oxygen ratio in the first bonding layer and the oxygen ratio in the second bonding layer. That is, although the amorphous layer is generated along the active surface of the support substrate, it is found that: due to the diffusion of oxygen in the amorphous layer, the oxygen ratio in the amorphous layer generated between the first bonding layer and the second bonding layer is sometimes higher than the oxygen ratio in the first bonding layer and the oxygen ratio in the second bonding layer. In addition, it is found that: when oxygen diffusion is performed in this way, the bonding strength of the piezoelectric material substrate on the support substrate is improved, for example, even when the piezoelectric material substrate is thinned by processing, the piezoelectric material substrate is not easily peeled off.
[0062] In a preferred embodiment, the difference between the oxygen ratio in the amorphous layer and the oxygen ratio in the first bonding layer and the difference between the oxygen ratio in the amorphous layer and the oxygen ratio in the second bonding layer are respectively 0.5 atomic % or more. The difference is more preferably 1.0 atomic % or more. The upper limit of the difference between the oxygen ratio in the amorphous layer and the oxygen ratio in the first bonding layer and the difference between the oxygen ratio in the amorphous layer and the oxygen ratio in the second bonding layer is not particularly limited, but is preferably 5.0 atomic % or less, and more preferably 4.5 atomic % or less.
[0063] In a preferred embodiment, the argon ratio in the amorphous layer is higher than the argon ratio in the first bonding layer and the argon ratio in the second bonding layer. If the microstructure promotes the diffusion of argon from each bonding layer to the middle amorphous layer, the bonding strength is further improved.
[0064] From the above viewpoints, the difference between the argon ratio in the amorphous layer and the argon ratio in the first bonding layer, and the difference between the argon ratio in the amorphous layer and the argon ratio in the second bonding layer are preferably 1.0 atomic % or more, and more preferably 1.5 atomic % or more. The upper limit of the difference between the argon ratio in the amorphous layer and the argon ratio in the first bonding layer, and the difference between the argon ratio in the amorphous layer and the argon ratio in the second bonding layer is not particularly limited, but is preferably 5.0 atomic % or less, and more preferably 4.5 atomic % or less.
[0065] In a preferred embodiment, the composition of the amorphous layer is mainly composed of silicon (Si), oxygen (O) and argon (Ar). Here, "as the main component" means that when the total atomic ratio is 100 atomic %, the total atomic ratio of the above atoms is 95 atomic % or more, more preferably 97 atomic % or more. It is particularly preferred that the composition of the amorphous layer is Si (1-t) O t (0.013≤t≤0.408), and the oxygen ratio is higher than that of the first bonding layer and the second bonding layer, and argon is contained.
[0066] The material of the intermediate layer between the supporting substrate and the first bonding layer and the intermediate layer between the piezoelectric material substrate and the second bonding layer can be any material that can be bonded to both, and there is no special limitation. Preferred materials include SiO2, Ta2O5, TiO2, ZrO2, HfO2, Nb2O3, Bi2O3, Al2O3, MgO, AlN, and Si3N4.
[0067] In particular, when facing high frequencies (such as the frequency band of 5G communication of 3.5 to 6 GHz), it is necessary to increase the frequency of elastic waves. In this case, the materials of the intermediate layer between the supporting substrate and the first bonding layer, and the intermediate layer between the piezoelectric material substrate and the second bonding layer are preferably high-speed acoustic materials. The sound velocity of the high-speed acoustic material is preferably above 6000 m / s, and more preferably above 10000 m / s. There is no particular limit on the upper limit of the sound velocity of each material of each intermediate layer. In fact, it is difficult to exceed 30000 m / s. Therefore, the upper limit is below 30000 m / s, and most of them are below 25000 m / s. As the high-speed acoustic material, AlN and Si3N4 can be exemplified. In addition, the sound velocity of the material is calculated based on the density (JIS C2141), Young's modulus (JISR1602), and Poisson's ratio (JIS R1602) measured by the JIS method.
[0068] In addition, when facing high frequencies (such as the frequency band of 5G communication of 3.5 to 6 GHz), since a high-power signal is input, it is necessary to improve the heat dissipation. In this case, it is preferred that the materials of the intermediate layer between the supporting substrate and the first bonding layer, and the intermediate layer between the piezoelectric material substrate and the second bonding layer are high thermal conductivity materials. The thermal conductivity of the high thermal conductivity material is preferably 100W / (m·K) or more, more preferably 900W / (m·K) or more, and particularly preferably 1000W / (m·K). There is no particular limit on the upper limit of the thermal conductivity of each material of each intermediate layer. In fact, it is difficult to exceed 5000W / (m·K), so the upper limit is 5000W / (m·K) or less, and most of them are 3000W / (m·K) or less. As the high thermal conductivity material, AlN and Si3N4 can be exemplified. In addition, the thermal conductivity of the material is measured in accordance with JIS R1611.
[0069] Hereinafter, each constituent element of the present invention will be further described.
[0070] The application of the bonded body of the present invention is not particularly limited, but it can be preferably applied to, for example, an elastic wave device and an optical device.
[0071] As elastic wave elements, surface elastic wave devices, Lamb wave devices, thin film resonators (FBARs), etc. are known. For example, in a surface elastic wave device, an IDT (Interdigital Transducer) electrode (also called a comb electrode or a curtain electrode) on the input side for exciting surface elastic waves and an IDT electrode on the output side for receiving surface elastic waves are provided on the surface of a piezoelectric material substrate. If a high-frequency signal is applied to the IDT electrode on the input side, an electric field is generated between the electrodes, exciting surface elastic waves and propagating on the piezoelectric material substrate. Furthermore, the propagated surface elastic waves can be output as electrical signals from the IDT electrode on the output side provided in the propagation direction.
[0072] The bottom surface of the piezoelectric material substrate may have a metal film. When manufacturing a Lamb wave element as an elastic wave device, the metal film plays a role in increasing the electromechanical coupling coefficient near the back surface of the piezoelectric material substrate. In this case, the Lamb wave element has the following structure: a comb-tooth electrode is formed on the surface of the piezoelectric material substrate, and the metal film of the piezoelectric material substrate is exposed by using a cavity provided in the supporting substrate. Examples of the material of such a metal film include aluminum, aluminum alloy, copper, gold, and the like. It should be noted that when manufacturing a Lamb wave element, a composite substrate having a piezoelectric material layer without a metal film on the bottom surface may be used.
[0073] In addition, a metal film and an insulating film may be provided on the bottom surface of the piezoelectric material substrate. When manufacturing a thin film resonator as an elastic wave device, the metal film plays the role of an electrode. In this case, the thin film resonator has the following structure: electrodes are formed on the surface and back of the piezoelectric material substrate, and the metal film of the piezoelectric material substrate is exposed by making the insulating film a cavity. Examples of materials for such a metal film include molybdenum, ruthenium, tungsten, chromium, and aluminum. In addition, examples of materials for the insulating film include silicon dioxide, phosphosilicate glass, borophosphosilicate glass, and the like.
[0074] In addition, examples of the optical element include an optical switch element, a wavelength conversion element, and a light modulation element. In addition, a periodic polarization inversion structure can be formed in the piezoelectric material substrate.
[0075] The object of the present invention is an elastic wave element. When the material of the piezoelectric material substrate is lithium tantalate, it is preferred to use a piezoelectric material substrate centered on the X-axis, which is the propagation direction of the surface elastic wave, and rotated from the Y-axis to the Z-axis by 36 to 47 degrees (for example, 42 degrees) because the propagation loss is small. In addition, when the piezoelectric material substrate contains lithium niobate, it is preferred to use a piezoelectric material substrate centered on the X-axis, which is the propagation direction of the surface elastic wave, and rotated from the Y-axis to the Z-axis by 60 to 68 degrees (for example, 64 degrees) because the propagation loss is small. Furthermore, the size of the piezoelectric material substrate is not particularly limited, for example, the diameter is 50 to 150 mm and the thickness is 0.2 to 60 μm.
[0076] In order to obtain the conjugate of the present invention, the following method is preferred.
[0077] First, each surface of each bonding layer is flattened to obtain a flat surface. Here, methods for flattening each surface include lap polishing, chemical mechanical polishing (CMP), etc. In addition, it is preferred that the flat surface has Ra ≤ 1 nm, and more preferably 0.3 nm or less.
[0078] Next, each surface of each bonding layer is cleaned to remove the residue of the abrasive and the deteriorated layer. The surface cleaning methods include wet cleaning, dry cleaning, brushing, etc. In order to obtain a clean surface simply and efficiently, brushing is preferred. At this time, it is particularly preferred to use Sunwash LH540 as a cleaning liquid, and then use a mixed solution of acetone and IPA to clean using a brush scrubber.
[0079] Next, each surface of each bonding layer is activated by irradiating the surface with a neutral beam.
[0080] When a neutral beam is used for surface activation, it is preferred to use the device described in patent document 3 to generate a neutral beam for irradiation. That is, as a beam source, a saddle-type high-speed atomic beam source is used. Then, an inert gas is introduced into the chamber, and a high voltage is applied to the electrode from a DC power supply. Thus, using the saddle-type electric field generated between the electrode (positive electrode) and the shell (negative electrode), the electron e moves and generates a beam of atoms and ions generated by the inert gas. In the beam that reaches the grid, the ion beam is neutralized in the grid, so a beam of neutral atoms is emitted from the high-speed atomic beam source. The atomic species that constitute the beam are preferably inert gases (argon, nitrogen, etc.).
[0081] When activation is performed by beam irradiation, the voltage is preferably 0.5 to 2.0 kV, and the current is preferably 50 to 200 mA.
[0082] Next, the activated surfaces are brought into contact and bonded in a vacuum atmosphere. The temperature at this time is room temperature, specifically, preferably 40°C or less, more preferably 30°C or less. In addition, the temperature during bonding is particularly preferably 20°C or more and 25°C or less. The pressure during bonding is preferably 100 to 20,000N.
[0083] Example
[0084] (Examples 1, 2, 3, 3-2, Comparative Examples 1, 2)
[0085] By reference Figure 1 and Figure 2 The bonded bodies 8 and 8A of the examples shown in Tables 1 and 2 were produced by the method described above.
[0086] Specifically, a lithium tantalate substrate (LT substrate) having an OF portion, a diameter of 4 inches, and a thickness of 250 μm was used as the piezoelectric material substrate 1. The LT substrate used was a 46° Y-cut X-propagation LT substrate of a cutting plate with a propagation direction of a surface elastic wave (SAW) as X and a cut-out angle of rotation Y. The surface 1a of the piezoelectric material substrate 1 was mirror-polished so that the arithmetic mean roughness Ra became 0.3 nm. Among them, Ra was measured with a field of view of 10 μm×10 μm using an atomic force microscope (AFM).
[0087] Next, a bonding layer 2 is formed on the surface 1a of the piezoelectric material substrate 1 by a DC sputtering method. Si doped with boron is used as a target. In addition, oxygen gas is introduced as an oxygen source. At this time, the total pressure and oxygen partial pressure of the atmosphere in the chamber are changed by changing the amount of oxygen introduced, thereby changing the oxygen ratio of the bonding layer 2. The thickness of the bonding layer 2 is set to 100 to 200 nm. The arithmetic mean roughness Ra of the surface 2a of the bonding layer 2 is 0.2 to 0.6 nm. Next, the bonding layer 2 is subjected to chemical mechanical polishing (CMP) to a film thickness of 80 to 190 nm and a Ra of 0.08 to 0.4 nm.
[0088] On the other hand, a support substrate 3 made of silicon having an orientation flat (OF) portion, a diameter of 4 inches, and a thickness of 500 μm was prepared as the support substrate 3. The surface of the support substrate 3 was finished by chemical mechanical polishing (CMP) so that the arithmetic mean roughness Ra was 0.2 nm.
[0089] Next, a bonding layer 4 is formed on the surface 3a of the supporting substrate 3 by a DC sputtering method. Si doped with boron is used as a target. In addition, oxygen gas is introduced as an oxygen source. At this time, the total pressure and oxygen partial pressure of the atmosphere in the chamber are changed by changing the amount of oxygen introduced, thereby changing the oxygen ratio of the bonding layer 4. The thickness of the bonding layer 4 is set to 100 to 200 nm. The arithmetic mean roughness Ra of the surface 4a of the bonding layer 4 is 0.2 to 0.6 nm. Next, the bonding layer 4 is subjected to chemical mechanical polishing (CMP) to a film thickness of 80 to 190 nm and a Ra of 0.08 to 0.4 nm.
[0090] Next, the surfaces of the bonding layer 2A and the bonding layer 4 are cleaned to remove dirt and then introduced into a vacuum chamber. -6 After the surface is above 100 Pa, each surface is irradiated with a high-speed atomic beam (acceleration voltage 1 kV, Ar flow rate 27 sccm) for 120 seconds. Then, the beam irradiation surface (activation surface) 5 of the bonding layer 2 and the activation surface 6 of the bonding layer 4 are brought into contact, and then a pressure of 10000 N is applied for 2 minutes to perform bonding (refer to Figure 3 (b)) Next, the obtained bonded body 8 of each example was heated at 100°C for 20 hours.
[0091] Next, the surface of the piezoelectric material substrate 1 was ground and polished so that the thickness was reduced from the initial 250 μm to 1 μm (see Figure 4 (a)).
[0092] The following characteristics were evaluated for the obtained bonded bodies 8 and 8A of each example.
[0093] (Confirmation of amorphous layer)
[0094] The presence of the amorphous layer was observed as follows.
[0095] Measurement device:
[0096] The microstructure was observed using a transmission electron microscope (H-9500 manufactured by Hitachi High-Technologies Corporation).
[0097] Determination conditions:
[0098] The sample sliced by the FIB (focused ion beam) method was observed at an accelerating voltage of 200 kV.
[0099] (Atomic Ratios in the First Bonding Layer, Amorphous Layer, and Second Bonding Layer)
[0100] Elemental analysis was performed using EDS (energy dispersive X-ray spectrometer) using the following apparatus to measure the ratios of oxygen atoms and argon atoms in the bonding layer and the amorphous layer.
[0101] Measurement device:
[0102] Elemental analysis was performed using an elemental analysis device (JEM-ARM200F, produced by JEOL Ltd.).
[0103] Determination conditions:
[0104] The sample sliced by the FIB (focused ion beam) method was observed at an accelerating voltage of 200 kV.
[0105] (Joint strength)
[0106] The joint strength of the joint bodies 8 and 8A of each example was measured by the crack opening method. 2 When the bonding layer is not peeled off, the bonded bodies 8 and 8A are mainly destroyed.
[0107] [Table 1]
[0108]
[0109] [Table 2]
[0110]
[0111] In Comparative Examples 1 and 2, the bonding strength was low.
[0112] In Examples 1, 2, 3, and 3-2, the oxygen ratio and argon ratio in the amorphous layer are higher than those in the first bonding layer and the second bonding layer, and the bonding strength is significantly improved, and no peeling occurs during the polishing of the piezoelectric material substrate. In Example 3-2, the argon ratio in the amorphous layer is higher than those in the first bonding layer and the second bonding layer, but the difference in the argon ratio is less than 1 atomic %, and the bonding strength is slightly lower than that in Examples 1, 2, and 3.
[0113] (Example 4, Comparative Example 4)
[0114] In Example 1, the material of the supporting substrate was changed to sapphire, and the FAB irradiation amount was also changed. In addition, the bonded bodies 8 and 8A were prepared in the same manner as in Example 1, and the oxygen ratio, argon ratio, silicon ratio and bonding strength of each part were measured. The results are shown in Table 3.
[0115] [Table 3]
[0116]
[0117] In Comparative Example 4, the oxygen ratio in the amorphous layer is slightly lower than the oxygen ratio in the first bonding layer and is the same as the oxygen ratio in the second bonding layer, and the bonding strength is low.
[0118] In Example 4, the oxygen ratio and argon ratio in the amorphous layer are higher than those in the first bonding layer and the second bonding layer, the bonding strength is significantly improved, and no peeling occurs during polishing of the piezoelectric material substrate.
[0119] (Example 5, Comparative Example 5)
[0120] In Example 1, the material of the support substrate was changed to cordierite, and the FAB irradiation amount was also changed. In addition, the bonded bodies 8 and 8A were prepared in the same manner as in Example 1, and the oxygen ratio, argon ratio, silicon ratio and bonding strength of each part were measured. The results are shown in Table 4.
[0121] [Table 4]
[0122]
[0123] In Comparative Example 5, the oxygen ratio in the amorphous layer was the same as the oxygen ratio in the first bonding layer and the second bonding layer, and the bonding strength was low.
[0124] In Example 5, the oxygen ratio and argon ratio in the amorphous layer are higher than those in the first bonding layer and the second bonding layer, the bonding strength is significantly improved, and no peeling occurs during polishing of the piezoelectric material substrate.
[0125] (Example 6, Comparative Example 6)
[0126] In Example 1, the material of the support substrate was changed to silicon aluminum oxynitride ceramic (z=2.5), and the FAB irradiation amount was also changed. In addition, the bonded bodies 8 and 8A were prepared in the same manner as in Example 1, and the oxygen ratio, argon ratio, silicon ratio and bonding strength of each part were measured. The results are shown in Table 5.
[0127] [Table 5]
[0128]
[0129] In Comparative Example 6, the oxygen ratio in the amorphous layer was the same as the oxygen ratio in the first bonding layer and slightly lower than the oxygen ratio in the second bonding layer, and the bonding strength was low.
[0130] In Example 6, the oxygen ratio and argon ratio in the amorphous layer are higher than those in the first bonding layer and the second bonding layer, the bonding strength is significantly improved, and no peeling occurs during polishing of the piezoelectric material substrate.
[0131] (Example 7, Comparative Example 7)
[0132] In Example 1, the material of the support substrate was changed to mullite, and the FAB irradiation amount was also changed. In addition, the bonded bodies 8 and 8A were prepared in the same manner as in Example 1, and the oxygen ratio, argon ratio, silicon ratio and bonding strength of each part were measured. The results are shown in Table 6.
[0133] [Table 6]
[0134]
[0135] In Comparative Example 7, the oxygen ratio in the amorphous layer was the same as the oxygen ratio in the first bonding layer and the second bonding layer, and the bonding strength was low.
[0136] In Example 7, the oxygen ratio and argon ratio in the amorphous layer are higher than those in the first bonding layer and the second bonding layer, the bonding strength is significantly improved, and no peeling occurs during polishing of the piezoelectric material substrate.
[0137] (Example 8, Comparative Example 8)
[0138] In Example 1, the material of the supporting substrate was changed to translucent alumina, and the FAB irradiation amount was also changed. In addition, the bonded bodies 8 and 8A were prepared in the same manner as in Example 1, and the oxygen ratio, argon ratio, silicon ratio and bonding strength of each part were measured. The results are shown in Table 7.
[0139] [Table 7]
[0140]
[0141] In Comparative Example 8, the oxygen ratio in the amorphous layer is slightly lower than the oxygen ratios in the first bonding layer and the second bonding layer, and the bonding strength is low.
[0142] In Example 8, the oxygen ratio and argon ratio in the amorphous layer are higher than those in the first bonding layer and the second bonding layer, the bonding strength is significantly improved, and no peeling occurs during polishing of the piezoelectric material substrate.
Claims
1. A conjugate, characterized in that: have: A supporting substrate; Piezoelectric material substrate; The first bonding layer is disposed on the support substrate and is composed of Si (1-x) O x , where 0.008≤x≤0.408; The second bonding layer is provided on the piezoelectric material substrate and is composed of Si (1-y) O y , where 0.008≤y≤0.408; and an amorphous layer, the amorphous layer being disposed between the first bonding layer and the second bonding layer, The oxygen ratio in the amorphous layer is higher than the oxygen ratio in the first bonding layer and the oxygen ratio in the second bonding layer.
2. The joint body according to claim 1, characterized in that: A difference between an oxygen ratio in the amorphous layer and an oxygen ratio in the first bonding layer and a difference between an oxygen ratio in the amorphous layer and an oxygen ratio in the second bonding layer are 0.5 atomic % or more.
3. The joint body according to claim 1 or 2, characterized in that: The argon ratio in the amorphous layer is higher than the argon ratio in the first bonding layer and the argon ratio in the second bonding layer.
4. The joint body according to claim 3, characterized in that: A difference between an argon ratio in the amorphous layer and an argon ratio in the first bonding layer, and a difference between an argon ratio in the amorphous layer and an argon ratio in the second bonding layer are 1 atomic % or more.
5. The joint body according to claim 1 or 2, characterized in that: The material of the support substrate is selected from the group consisting of silicon, silicon aluminum oxynitride ceramics, sapphire, cordierite, mullite and alumina.
6. The joint body according to claim 1 or 2, characterized in that: The material of the piezoelectric material substrate is selected from the group consisting of lithium niobate, lithium tantalate, and lithium niobate-lithium tantalate solid solution.
7. The joint body according to claim 1 or 2, characterized in that: The bonded body includes an intermediate layer provided between the supporting substrate and the first bonding layer.
8. The joint body according to claim 1 or 2, characterized in that: The bonded body includes an intermediate layer provided between the piezoelectric material substrate and the second bonding layer.
9. An elastic wave element, characterized in that: The invention comprises: the bonded body according to any one of claims 1 to 8, and electrodes provided on the piezoelectric material substrate.
Citation Information
Patent Citations
[kiyoujiseisankatetsunoseihou[kiyoujiseisankatetsunoseihou]
JP1983014727B2
Method of manufacturing surface acoustic wave element
JP2004343359A
Bonded body and acoustic wave element
WO2018180827A1